α4β7 Integrin Antagonist Vedolizumab for the Treatment of Refractory Ileitis - Rafał Filip; Błażej Goliat; Małgorzata Dziechciaż; Piotr Dąbrowski; Michał Osuchowski; Piotr Paluszkiewicz (Case Reports in Gastrointestinal Medicine)
Background and Aims. Ulcerative colitis (UC) is a superficial diffuse inflammation restricted to the colon and rectum. Inflammation within the small bowel may occur several years after a pancolectomy. The pathogenesis is unknown and seems to be different from Crohn’s disease or other causes of diseases of the small intestine, but an association with colectomy due to UC is very likely. Methods and Results. We describe the case of a patient with a probable diagnosis of pan-UC accompanied by Sjögren’s syndrome and partial IgA deficiency, who developed enteritis after a restorative pancolectomy. For induction and maintenance of remission, the patient was successfully treated with mycofenolate mofetil (MMF) and vedolizumab (VDZ). Conclusions. We suggest that a previously refractory to standard therapy UC-related enteritis can be treated with combination MMF and VDZ.